ANALYSIS OF TRENDS IN THE DEVELOPMENT OF INFORMATION MANAGEMENT SYSTEMS BASED ON RESEARCH AND DEVELOPMENT (Web of Teachers: Inderscience Research, 2025)
This study examines the trends in the development of information management systems (IMS) based on the latest research and development (R&D). Special attention is given to the analysis of key technologies such as artificial intelligence, cloud computing, blockchain, and the Internet of Things, as well as their impact on management efficiency and decision-making. The study covers the main challenges arising from the implementation of new technologies, including cybersecurity, integration complexity, and high costs. Furthermore, the paper explores the evolution of IMS architecture, including the transition from centralized systems to decentralized and hybrid models, which enhance resilience and adaptability. Approaches to optimizing decision-making processes through the application of intelligent data processing and forecasting algorithms are analyzed. Additionally, socio-economic aspects of IMS implementation are considered, such as the impact on the labor market, changes in corporate governance, and new models of interaction between users and systems. The study providing a comprehensive analysis of methodologies, results, and discussions related to technological advancements, implementation challenges, and future prospects in this field. The research findings may be useful for scientists, developers, and business analysts involved in designing and optimizing IMS, as well as for policymakers and regulators shaping digital transformation strategies across various industries.